Analisis Risiko Proyek Pembangunan Relokasi Jalan Nasional Mempawah – Sungai Duri Kalimantan Barat Menggunakan Metode Bow Tie Analysis - Dhuha, Syamsud; Artama Wiguna, I Putu (Fakultas Ekonomi Universitas Gresik, 2023)
The National Road Relocation Development Project in Mempawah, West Kalimantan, functions as a substitute for a national road that will later be affected by the construction of the Kijing International Port in Mempawah Regency, West Kalimantan Province. Current conditions in the field have found several problems that impede the achievement of progress, which poses several risks. This study aims to analyze the highest level of risk from several identified risks. This is why it is important to conduct a risk analysis study on the National Road Relocation Project. This research method uses a qualitative and quantitative approach, starting with the identification of risks in similar projects, then proceeding to test the relevance of risks that may occur and the impact of those risks. Data collection methods were carried out by distributing questionnaires, conducting focus group discussions, and conducting interviews. Furthermore, quantitative analysis was carried out with response scenarios and Bowtie analysis. The results of this study identified the six highest risks: conditions and field data not in accordance with the design, design changes during the project, land for work that has not been acquired, bad weather disturbances, cost overruns, and material price increases. Contingency costs incurred amount to Rp. 15,757,472,740, or 8.34% of the project value, which is Rp. 188,909,724,300.